Macroscopic quantum phenomena in Josephson structures - Barone, A.; Lombardi, F.; Rotoli, G.; Tafuri, F. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2010)
The Josephson effect is a probe of unparalleled performances in the study of a variety of macroscopic quantum phenomena. In the present article an overview of important achievements and challenging trends is given referring, in particular, to macroscopic quantum tunneling and energy level quantization. The attention is mainly addressed to high-TC superconducting structures and recent investigations concerning nanostructures.